2022
DOI: 10.3389/fphar.2022.933096
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics and Metabolomics Unveil Codonopsis pilosula (Franch.) Nannf. Ameliorates Gastric Precancerous Lesions via Regulating Energy Metabolism

Abstract: Objective: This study aimed to systematically evaluate the efficacy of Codonopsis pilosula (Franch.) Nannf. (Codonopsis Radix, CR) and reveal the mechanism of its effects on suppressing Gastric Precancerous Lesions.Methods: First, we established the GPL rat model which was induced by N-methyl-N′-nitro-N-nitrosoguanidine, a disordered diet, and 40% ethanol. The CR’s anti-Gastric Precancerous Lesions effect was comprehensively evaluated by body weight, pathological section, and serum biochemical indexes. Then, q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…0.04 mol L −1 MNNG solution at 5 mL kg −1 was administered via gavage every three days and irregular diets (2 d satiety, l d starvation, 3 d cycle) were used to develop the CNAG rat model. 10 CNAG is characterized by an infiltration of inflammatory cells ( e.g. neutrophils and monocytes) in the mucosal layer and the degree of inflammation is graded according to the intensity and depth of the infiltration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…0.04 mol L −1 MNNG solution at 5 mL kg −1 was administered via gavage every three days and irregular diets (2 d satiety, l d starvation, 3 d cycle) were used to develop the CNAG rat model. 10 CNAG is characterized by an infiltration of inflammatory cells ( e.g. neutrophils and monocytes) in the mucosal layer and the degree of inflammation is graded according to the intensity and depth of the infiltration.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitative proteomics and metabolomics results showed that aqueous extract of Dangshen inhibited the proliferation of gastric cancer cells by regulating energy metabolism, and that serum containing Dangshen inhibited the proliferation of gastric cancer AGS cells without a significant effect on normal gastric mucosal epithelial cells. 10 Further study revealed that polysaccharides of Dangshen could effectively inhibit the proliferation of gastric cancer AGS cells, induce apoptosis and inhibit the secretion of pro-inflammatory factors, the mechanism of which may be related to the regulation of the miR-361-5p/ TLR4/NF-κB pathway. 11 Based on the above study, we propose the hypothesis that DHJ may have a protective effect on the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…Alzheimer’s disease (AD) is a gradual progressive neurological disorder, and CP can be used to improve nerve cell function and reduce neurodegeneration, which helps to slow down the development of Alzheimer’s disease ( Xie et al, 2024 ). Colon cancer ( Cao Y. et al, 2019 ), gastric precancerous lesions ( He et al, 2022 ), liver cancer ( Liu Z. et al, 2022 ; Li N. et al, 2024 ), hepatitis ( Zeng et al, 2023 ), and colitis ( Li F. et al, 2024 ) are malignant tumors or inflammatory diseases of the digestive system, and CP plays an important role in preventing and treating these diseases play an important role. Interestingly, CP can also regulate the immune function of sepsis ( Choi et al, 2023 ), rheumatoid arthritis ( Wang Y.-J.…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%
“…Lobetyolin and lobetyol are the main active anti-tumor components of Codonopsis lanceolata , Codonopsis lanceolata Polyacetylenes induces apoptosis in lung cancer cells and ameliorates lung dysfunction by inactivating the Ras/PI3K/AKT pathway ( Wang et al, 2022 ). CPPs inhibit MCF-7 cell proliferation and induce apoptosis through downregulation of CCHE1 expression ( He R. et al, 2022 ).…”
Section: Pharmacological Effectsmentioning
confidence: 99%